SEUSS Integrates Gibberellin Signaling with Transcriptional Inputs from the SHR-SCR-SCL3 Module to Regulate Middle Cortex Formation in the Arabidopsis Root . Issue 3 (27th January 2016) - Gong, Xue; Flores-Vergara, Miguel A.; Hong, Jing Han; Chu, Huangwei; Lim, Jun; Franks, Robert G.; Liu, Zhongchi; Xu, Jian
Abstract : The transcription factor SEU promotes middle cortex formation through a network of transcription factor interactions. Abstract: A decade of studies on middle cortex (MC ) formation in the root endodermis of Arabidopsis ( Arabidopsis thaliana ) have revealed a complex regulatory network that is orchestrated by several GRAS family transcription factors, including SHORT-ROOT (SHR), SCARECROW (SCR), and SCARECROW-LIKE3 (SCL3). However, how their functions are regulated remains obscure. Here we show that mutations in the SEUSS ( SEU ) gene led to a higher frequency of MC formation. seu mutants had strongly reduced expression of SHR, SCR, and SCL3, suggesting that SEU positively regulates these genes. Our results further indicate that SEU physically associates with upstream regulatory sequences of SHR, SCR, and SCL3 ; and that SEU has distinct genetic interactions with these genes in the control of MC formation, with SCL3 being epistatic to SEU . Similar to SCL3, SEU was repressed by the phytohormone GA and induced by the GA biosynthesis inhibitor paclobutrazol, suggesting that SEU acts downstream of GA signaling to regulate MC formation. Consistently, we found that SEU mediates the regulation of SCL3 by GA signaling. Together, our study identifies SEU as a new critical player that integrates GA signaling with transcriptional inputs from the SHR-SCR-SCL3 module to regulate MC formation in the Arabidopsis root.